Traditional Ledership in Negeri Tulehu: Transformation and Dynamics in the Modern Context - Tuanaya, Wahab; Layn, Safrudin Butsma; Wance, Marno (Department of Government Studies, Universitas Muhammadiyah Buton., 2024)
This study aims to examine issues related to the existence of traditional leadership in Tulehu, Central Maluku Regency, particularly in the context of conflicts that occurred during the election of the king or village head. The main focus of this study is on the delay in the ratification of the King by the Regent of Central Maluku, the protests by the community against the decision to appoint a King who did not follow the lineage of the matarumah Ohorella, and the decision of the Saniri Negeri that did not base the selection of the King on the royal lineage. This study uses a qualitative method with a descriptive analytical approach and was conducted over a period of five months. Data collection techniques include interviews, direct observation, and documentation of various primary and secondary sources. The results of this study indicate that local government officials need to strengthen their role as traditional leaders who have strong legitimacy among the community. The Saniri Negeri plays an important role in maintaining the traditional selection process based on royal lineage (matarumah perintah), which contributes to social stability and harmonious relations among citizens. The implications of these findings indicate the importance of collaboration between the government and traditional institutions in resolving leadership conflicts in order to create a government that is accepted by all elements of society. However, the limitations of this study lie in its scope, which is restricted to one region, as well as the limited time available to capture dynamics that may arise after the study period ends. Further studies are recommended to cover a broader geographical area and timeframe to gain a more comprehensive understanding.